Pembuatan Desain Kemasan Menggunakan Aplikasi Corel Draw untuk Meningkatkan Minat Beli pada Setiawan Meat Kota Batu - Reyhan Hadani Setiawan; Heru Utomo; Dwi Sudjanarti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Setiawan Meat is a business specializing in selling of raw beef, operating with a commitment to providing high-quality products to consumers. One of Setiawan Meat’s innovative products is frozen food. This innovation aims to follow the ever-changing market trends and meet the customers need. Relate to that, the purpose of this study was to design packaging that can increase the customer buying interest in Setiawan Meat products. This study used the Action Research method, which consists of planning, action, observation, and reflection. The data collection methods included observation, interviews, and documentation. The unit of analysis included 1 owner, 2 marketing experts, 2 computer experts, and 10 consumers. The effectiveness of the design was measured with the EPIC model, which includes the dimensions of Empathy, Persuasion, Impact, and Communication. The purchase interest was measured with the AIDA model, which includes the stages of Attention, Interest, Desire, and Action. The results showed that in cycle 1, the packaging design was already in the "very effective" category, but there were still some suggestions and feedback from the respondents. Therefore, the design needed to be improved in the next cycle. In cycle 2, the EPIC score averaged 4.57, which belong to the "very effective" range. The AIDA results showed that all statements scored above 80%, with an average of 90.27%, indicating that respondents strongly agreed with the packaging design and considered it suitable for publication. Based on the results of the study, it can be concluded the packaging design created with CorelDraw is very effective to increase the buying interest. It is expected that this packaging design can be well utilized and help Setiawan Meat enhance customer purchase interest and sales of  frozen food products.